Strategi pengelolaan risiko setelah lonjakan NPF periode 2020-2024: Studi empiris pada Bank Muamalat Indonesia - Maulana, Muhammad Mudzakkir; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2026)
Islamic banking plays an important role in building a financial system that is stable, fair, and compliant with Sharia principles. One way to determine the financial soundness of an Islamic bank is through the Non-Performing Financing (NPF) ratio, which measures the proportion of problematic financing compared to the total financing provided. This ratio can be used to assess the bank’s asset quality and evaluate how effectively it manages financing risks. Bank Muamalat Indonesia, as the first Islamic bank in the country, has also faced challenges in maintaining the quality of its financing, especially during the period from 2020 to 2024, which was influenced by the COVID-19 pandemic, economic recovery processes, and changes in the bank’s internal operations.banks.